IMPROVING ENGLISH SPEAKING SKILL BY USING ROLE-PLAY METHOD THROUGH MULTIMEDIA DEVICES IN CLASS X STUDENTS (CLASSROOM ACTION RESEARCH AT SMAN 1 PRABUMULIH) - Uzer, Yuspar; Uzer, Yus Vernandes; Hidayad, Ferri (Politeknik Negeri Sriwijaya, 2022)
transfer their ideas to other people. One of the difficulties faced by English learners is the inability to engage in conversation. Some students neglect to speak because they are too shy or because they have a high level of anxiety about talking. In this case, the researchers used Role- Play as a method in teaching and learning process to solve the students’ problem. The objective of the research was to describe how can role-play method improve English speaking skill through multimedia devices in class X students of SMAN 1 Prabumulih. This research was conducted at tenth grade of SMAN 1 Prabumulih. It used classroom action research (CAR) divided into two cycles. The result of the first cycle showed the mean score was 63.5%, which meant there were only six students who passed the target score of 70. Whereas the result of the second cycle was 75, it meant that the students had improved their score in speaking. Therefore, it could be concluded that there was an improvement in students' speaking skills after using role-play through multimedia devices. Keywords: Multimedia devices, speaking, role-play method